2016
DOI: 10.4103/2230-8210.190539
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and microbiological profile of the diabetic hand: A retrospective study from South India

Abstract: Background:Pyogenic Infections of the hand in diabetes are largely a tropical entity and published material in the area are rather meagre.Patients and Methods:This is a retrospective study on the pattern of hand infections and involves the microbiological profile of 39 cases of diabetes hand-related infections admitted to the hospital between the years 2004 and 2010.Results:This study included 39 patients, among whom 23 (59%) had necrotizing fasciitis (NF), and 16 (9-abscess and 7-tenosynovitis) had nonnecroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…This led to an amputation rate of 18% in the study cohort, with significant factors contributing to the worse prognosis in patients with DM being evidence of poor glycemic control, delayed presentation, and prior intervention for hand infection. 23 In our study, patients with DM were found to have a slightly increased likelihood to need more than one I&D and an increased LOS on multivariate linear regression.…”
Section: Discussionmentioning
confidence: 50%
“…This led to an amputation rate of 18% in the study cohort, with significant factors contributing to the worse prognosis in patients with DM being evidence of poor glycemic control, delayed presentation, and prior intervention for hand infection. 23 In our study, patients with DM were found to have a slightly increased likelihood to need more than one I&D and an increased LOS on multivariate linear regression.…”
Section: Discussionmentioning
confidence: 50%
“…Conversely, several previous reports from Asian countries have reported male dominance11. These observations are believed to be due to the fact that in many African communities, women make up the majority of the manual labour work force as opposed to men in Southwest China and India11,12. Consequently, African females are more likely to suffer minor hand trauma that could predispose these individuals to infections.…”
Section: Discussionmentioning
confidence: 96%
“…We looked up the Indian studies on diabetic hand infections and found that in the study by Raveendran et al 5 the study population consisted of 39 cases admitted in their center over 6 years. The profile showed a male preponderance: 24/39 patients (61.5%).…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 4 A PubMed search for articles on diabetic hand infection from India provided three retrievable original articles; one each from the northern, eastern and southern parts of India. 5 6 7 One of the main concerns among patients with diabetic hand infections is the risk of amputation and multiple surgical procedures which, in turn, influence the length of inpatient stay and the cost of care, which are the second common concern of the patients. This study was intended to find out the factors present at the time of arrival, which have a significant relationship with the risk of amputation and multiple surgical procedures.…”
Section: Introductionmentioning
confidence: 99%